Vaccines for Neglected Pathogens: Strategies, Achievements and Challenges Focus on Leprosy, Leishmaniasis, Melioidosis and Tuberculosis - Christodoulides, Myron (Springer International Publishing : Imprint: Springer, 2023)
This book reviews successes and (remaining) challenges in vaccine development for the selected Neglected Tropical Diseases (NTD) of Leprosy, Leishmaniasis, Meliodoisis and Tuberculosis, which are a continuous burden for millions of people in affected areas worldwide. Written by frontline researchers, the volume deep-dives into different vaccine strategies, provides biotechnological background information and also tackles animal models in NTD therapeutics research. By bringing together state-of-the-art expert knowledge, the book contributes to the aim of ultimately ending the epidemics of neglected tropical diseases, complying with UN Sustainable Development Goal 3, Health and Well-Being.The volume highlights the activities of the research network VALIDATE (VAccine deveLopment for complex Intracellular neglecteD pAThogEns), funded by the Medical Research Council in the UK. The four NTDs discussed in the book were selected as these are in the focus of VALIDATE's research. The book targets scientists and clinicians working on NTDs, as well as all readers with a background in biomedicine and interest in vaccine development. This is an open access book.